2014
DOI: 10.1002/cmdc.201300490
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Fluorination of a Nonsteroidal Anti‐inflammatory Drug to Prolong Metabolic Half‐Life

Abstract: (2014) 'Targeted uorination of a nonsteroidal anti-in ammatory drug to prolong metabolic half-life.', ChemMedChem., 9 (4). pp. 733-736. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The use of deuterium can also have the unintended consequence of imparting stability to the label that the analyte does not have [96]. Unlike a 13 C, 15 N or 18 O isotope, primary and secondary kinetic isotope effects using deuterium can be significant.…”
Section: Key Termmentioning
confidence: 96%
“…The use of deuterium can also have the unintended consequence of imparting stability to the label that the analyte does not have [96]. Unlike a 13 C, 15 N or 18 O isotope, primary and secondary kinetic isotope effects using deuterium can be significant.…”
Section: Key Termmentioning
confidence: 96%
“…However, no The site of fluorine substitution had an influence on the extent of oxidation; thus compound 2, in which the fluorine is at C-3', was almost entirely biotransformed after 24 h incubation with C. elegans, whereas compound 3 (fluorine at C-2') was biotransformed to a much lesser degree and compound 4 (fluorine at C-4') was not biotransformed at all. Based on our previous studies with the related substrates fluorobiphenyl Murphy, 2010, Bright et al, 2013) and flurbiprofen , Shaughnessy et al, 2014, the 4' position is predominantly hydroxylated and if replaced with fluorine, no hydroxylation is observed, which would account for the absence of hydroxylation of 4. Furthermore, 2, 3 and 5 were similarly regiospecifically hydroxylated at C4' by the fungus.…”
Section: Mammalian Biotransformation Of Fluorophenyl Pyridine Carboxymentioning
confidence: 96%
“…Our previous studies on biphenyl systems , Bright et al, 2013, Shaughnessy et al, 2014 demonstrated that the hydroxylation typically occurs on the 4' (para) position. Furthermore, when this site is blocked by fluorine, no hydroxylation occurs, and the observation that 4 was not biotransformed by the fungus is consistent with this.…”
Section: Site Of Mono-hydroxylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is beneficial because of the rather limited space in the S 1 ′ pocket. The para ‐fluorinated compound was of highest interest to us, as it does not display a hydrogen atom in the para position, which is prone to metabolic degradation by cytochrome P450 enzymes . Driven by the promising results derived from the molecular design approach, we synthesized compounds 2 a – g (Figure ) in order to test our hypotheses with biological inhibitory data (Table ).…”
Section: Figurementioning
confidence: 99%